South America between two turns.: Debates and lectures about the (again) new political map - Quiroga, María Virginia (Universidad Nacional de Villa María, 2018)
This article attempts to systematize a set of researches and interpretations about the South American´s political map, trough over the last two decades. The new century showed the emergence and consolidation of Governments which represent a “left turn”, taking distance from the neoliberal precepts and making an approach with the active social mobilization. Many discussions have been established about the best ways of nominating this new cycle; however, “progressive” governments seems to be losing territory and strength. Beyond the diversity of diagnoses, from 2015 until our days, the regional map is leading with a “right turn”, which presents new questions and challenges.